Immunoproteasome expression is associated with better prognosis and response to checkpoint therapies in melanoma - Shelly Kalaora (Nature Portfolio, 2020)
The response to immunotherapy of melanoma patients is heterogeneous. Here, the authors demonstrate that a high expression of the two major components of the immunoproteasome, PSMB8 and PSMB9, modulates the production of HLA peptides and it is predictive of better survival and improved response to immune-checkpoint inhibitors of melanoma patients.